(untitled) (Research, Society and Development, 2023)
Hyaluronic acid (HA) is an endogenous substance present in various tissues and biological fluids. Due to its physicochemical properties, it contributes to many biological processes at intra and extracellular levels, such as skin hydration, joint lubrication and wound healing, in addition to its anti-inflammatory and antioxidant effects. For this reason, HA has been applied as an anti-aging molecule in the form of cosmetic products. In this way, the present article aimed, through a bibliographic review, to describe the benefits of the different pharmaceutical forms with hyaluronic acid in the management of skin aging. This is a narrative review of the literature, which allowed the authors to present the different attributes of hyaluronic acid in different pharmaceutical formulations in the fight against aging. As a technical procedure, the health descriptors “hyaluronic acid”, “pharmaceutical forms”, “benefits of hyaluronic acid” and “indications with hyaluronic acid” were used. The results obtained allowed observing that hyaluronic HA has become one of the most promising actives against skin aging, being present in different cosmetic formulations, and can be found in moisturizers and protectors. Therefore, the evidence on the results allows us to state that the different pharmaceutical forms containing HA result in several benefits in preventing skin aging.